Interoceptive Awareness Mediates Effects of Sleep Disturbance on Pain Outcomes in Chronic Pain Patients - Dana Dharmakaya Colgan; Natasha Parman (Integrative Medicine Reports)
Background: Sleep disorders are common in adults with chronic pain and are multifactorial. Recent evidence suggest sleep disturbance may affect interoceptive awareness (IA) in healthy adults. Less is known about the relationship between IA, sleep, and pain in adults with chronic pain. Purpose: This cross-sectional study investigated the relationships between perceived sleep disruption (PROMIS Sleep), pain interference (PROMIS Pain Interference Short Form), pain intensity (PROMIS Pain Intensity Scale), and IA (Multidimensional Interoceptive Awareness Scale-2 [MAIA-2]), and subsequently, delineated potential direct and indirect links among constructs. Methods: Online surveys were administered to 301 individuals with chronic pain. Strategic sampling targeted respondents to reflect the 2010 census. Pearson’s correlation characterized the overall relationship between variables. Hierarchical multiple regression analyses were conducted to investigate direct links between sleep disturbance, pain outcomes, and IA. Path analyses assessed mediational effects of IA on the relationship between sleep disturbance and pain outcomes. Results: Increased perceptions of sleep disturbance predicted increased pain interference (p ≤ 0.001, β = 0.42), increased pain intensity (p ≤ 0.001, β = 0.36), and reduced IA (p ≤ 0.001, β = −0.38) when controlling for pain duration. IA partially mediated the relationship between sleep disturbance and pain interference (point estimate = 0.16; 95% bootstrap confidence interval [CI] = 0.08–0.24) and between sleep disturbance and pain intensity (point estimate = 0.06; 95% bootstrap CI = 0.02–0.09). Conclusions: Findings show increased sleep disturbance predicted increased pain interference and increased pain intensity and reduced IA, and that IA partially mediated the relationship between sleep disturbance and pain characteristics. Findings support future research to explore causal relationships of these variables in longitudinal studies.